2011
DOI: 10.1007/s10880-011-9265-0
|View full text |Cite
|
Sign up to set email alerts
|

Adversarial Growth in Patients with Multiple Sclerosis and their Partners: Relationships with Illness Perceptions, Disability and Distress

Abstract: The purpose of this study was to investigate whether patients with multiple sclerosis (MS) and their partners show adversarial growth and to examine which psychological and disability variables contribute to this in patients and their partners. The study also investigated the relationship between growth and distress. Seventy-two patients with MS and their partners provided demographic information and completed measures of posttraumatic growth, illness perceptions, depression, cognitive function and disability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 38 publications
2
34
2
1
Order By: Relevance
“…It has been reported in some studies that patients with severe conditions perceiving positive changes were more likely to experience growth and also a better quality of life (Carroll, 2014). The findings of this study are also in agreement with several studies exploring posttraumatic growth in patients with MS. For example, Ackroyd et al, (2011) found a higher growth in these patients following the diagnosis of illness.…”
Section: Discussionmentioning
confidence: 91%
“…It has been reported in some studies that patients with severe conditions perceiving positive changes were more likely to experience growth and also a better quality of life (Carroll, 2014). The findings of this study are also in agreement with several studies exploring posttraumatic growth in patients with MS. For example, Ackroyd et al, (2011) found a higher growth in these patients following the diagnosis of illness.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, psychological distress before the intervention was higher among participants who experienced some sort of benefit during the program component compared with those who did not. While some studies have reported that greater levels of depression are associated with less benefit finding (Ackroyd et al., ), Calhoun and Tedeschi () claim that distress and growth after adversity exist in different dimensions. One can argue that benefit finding tends to be experienced more by people who have experienced significant pain, which frequently produces severe distress.…”
Section: Discussionmentioning
confidence: 99%
“…As many studies have demonstrated a positive relationship between benefit finding and adjustment across a range of chronic physical illnesses (Helgeson, Reynolds, & Tomich, ; Linley & Joseph, ), some researchers have suggested that benefit finding can restore one's meaning and also facilitate adjustment (Costa & Pakenham, ). Some researchers have even suggested that benefit finding can predict the quality of life (Brand, Barry, & Gallagher, in press); however, no consensus has yet emerged regarding the relationship between benefit finding and depression (Ackroyd et al., ).…”
mentioning
confidence: 99%
“…When a spousal partner has multiple sclerosis (MS), a demyelinating disease of the central nervous system with an unpredictable clinical course, navigating intimate relationships may be both challenging and rewarding. Couples dealing with MS have identified positive outcomes for their relationship, such as personal growth through facing adversity and other challenges together (Ackroyd et al, ). Couples identified personal growth as a benefit of living with MS and that each partner's growth depended on the other, an indication that couples search for and find meaning together (Ackroyd et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Couples dealing with MS have identified positive outcomes for their relationship, such as personal growth through facing adversity and other challenges together (Ackroyd et al, ). Couples identified personal growth as a benefit of living with MS and that each partner's growth depended on the other, an indication that couples search for and find meaning together (Ackroyd et al, ). Partners in caring roles described strengthening of relationships in general as a positive outcome (Pakenham, ).…”
Section: Introductionmentioning
confidence: 99%